Genotyping of African swine fever virus (ASFV) isolates associated with disease outbreaks in Uganda in 2007 - Carmina Gallardo; Anna R. Ademun2; Raquel Nieto; Noelina Nantima; Marisa Arias; Elena Martín; Virginia Pelayo; Richard P. Bishop (African Journal of Pig Farming, 2014)
Samples from infected domestic pigs associated with an outbreak of African swine fever (ASF) in three districts of central Uganda in 2007 were confirmed as being infected with African swine fever virus (ASFV) using a P72 genebased polymerase chain reaction amplification (PCR) assay combined with restriction analysis. None of the sera collected from pigs with clinical symptoms were positive using the OIE serological prescribed tests. However, seven haemadsorbing viruses were isolated in macrophage culture and genotyped by partial p72 and full length p54-gene sequencing. Four of these viruses were isolated directly from serum samples. All the viruses were classified within the domestic-pig cycle- associated p72 and p54 genotype IX which also includes viruses responsible for ASF outbreaks in Kenya in 2006 and 2007 and Uganda in 2003. To define virus relationships at higher resolution, typing was performed by analysis of tetrameric amino acid repeat regions within the central variable region (CVR) of the B602L gene. Ugandan isolates sequences exhibited 100% identity to viruses isolated from outbreaks in Kenya in 2007. The identity was greater than the viruses obtained from an earlier outbreak in Kenya in 2006. This provides further evidence that genetically similar ASFV virus within p72 Genotype IX may be circulating between Kenya and Uganda.